2004
DOI: 10.1542/peds.2004-0455
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Multistage Asthma Case-Detection Procedure for Elementary School Children

Abstract: ABSTRACT. Objective. The purpose of this study was to validate a 3-stage asthma case-detection procedure for elementary school-aged children.Methods. The study was performed in 10 elementary schools in 4 inner-city school systems, with a total enrollment of 3539 children. Results of the case-detection procedure were compared with the diagnosis of an asthma specialist study physician, to determine the sensitivity and specificity of the case-detection procedure.Results. Ninety-eight percent of children returned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…However, such an observation is not isolated. In addition to the absence of respiratory symptoms as determined by questionnaire, some patients do not report their symptoms even during medical examination [20,23,25]. The finding could reflect a low parental concern over these symptoms in a child, low readiness to report mild, intermittent symptoms or insufficient ability to recognize the symptoms especially if their severity is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such an observation is not isolated. In addition to the absence of respiratory symptoms as determined by questionnaire, some patients do not report their symptoms even during medical examination [20,23,25]. The finding could reflect a low parental concern over these symptoms in a child, low readiness to report mild, intermittent symptoms or insufficient ability to recognize the symptoms especially if their severity is low.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation was based on reference values established by Dockery and Hsu [17,18]. The submaximal exercise challenge step test was completed according to the protocol described by Gerald et al [19,20]. Briefly, the child stepped up and down on a single step maintaining a heart rate between 150-200 beats per minute for five minutes.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Study design is shown in Fig. 1 (27), was used. A sub-maximal exercise test (stepping up and down on a single step with metronome rhythm) was followed by spirometry obtained at minutes 3, 5 and 10 after exercise.…”
Section: Participantsmentioning
confidence: 99%
“…Lung function was considered normal if FEV 1 , FVC and PEF values were at least 80% of predicted values, and the FEV 1 /FVC ratio was greater than 75%. Bronchial hyperresponsiveness was examined using an exercise challenge test [12]. The procedure of the sub-maximal exercise test involved stepping up and down on a single step with metronome rhythm.…”
Section: Methodsmentioning
confidence: 99%